Ice and the origin of life - Trinks, Hauke; Schröder, Wolfgang; Biebricher, Christof (Springer, 2005)
Sea ice occurs abundantly at the polar caps of the Earth and, probably, of many other planets. Its static and dynamic properties that may be important for prebiotic and early biotic reactions are described. It concentrates substrates and has many features that are important for catalytical actions. We propose that it provided optimal conditions for the early replication of nucleic acids and the RNA world. We repeated a famous prebiotic experiment, the poly-uridylic acid-instructed synthesis of polyadenylic acid from adenylic acid imidazolides in artificial sea ice, simulating the dynamic variability of real sea ice by cyclic temperature variation. Poly(A) was obtained in high yield and reached nucleotide chain lengths up to 400 containing predominantly 3' → 5' linkages.